REWORKING VULNERABILITIES: LINGUISTIC RESURRECTIONS OF FEMININE IDENTITY (Proceedings of the World Conference on Women’s Studies, 2023)
Language and linguistics are critical for exploring the ways in which society tends to perpetuate discrimination against women. The primary concern of this study is to analyze how female respondents understand oppressive patriarchal practices that they encounter in real life and how their language reflects their own orientation to their vulnerable position. In particular, it seeks to discover how language, as deeply embedded in the social construction of reality, helps women to mitigate patriarchal assumptions and practices thereby establishing a more egalitarian social standing. This study analyzes three narratives by female respondents from  different socio-economic strata and occupations. The experiences they describe range from dress codes at work to reproductive rights and vulnerability associated with being in the public sphere. Their life experiences capture various facets of oppression including cultural imperialism, powerlessness and exploitation, but the way they use language to navigate this oppression helps with resurrecting feminine identity. The data for this study has been collected from 3 female Hindi/Assamese respondents (aged between early twenties to  mid-forties for a representative sample of issues faced by women in adult life). The study uses a discourse analysis framework within a qualitative approach to explore women’s lived experiences both the private and the public sphere. The analysis shows that women’s resurrection of their social standing is made possible by their use of language, which can mitigate their vulnerabilities thereby redefining their identities in more positive light.Keywords: patriarchal oppression, feminine identity, vulnerabilities, resurrection, language,  discourse
Keywords: patriarchal oppression; feminine identity; vulnerabilities; resurrection; language; discourse